Glass rod-sliding and low pressure assisted solution processing composition engineering for high-efficiency perovskite solar cells - Wang, Duo; Wu, Cuncun; Luo, Wei; Guo, Xuan; Qi, Xin; Zhang, Yuqing; Zhang, Zehao; Qu, Bo; Xiao, Lixin; Chen, Zhijian (SOLAR ENERGY MATERIALS AND SOLAR CELLS, 2020)
High-efficiency perovskite solar cells (PSCs) have experienced rapid development and attracted significant attention in recent years. The PSCs based on doctor bladed or slot-die coated perovskite films usually have lower power conversion efficiency (PCE) than that based on spin-coated perovskite films. In this work, we have developed an effective method, called glass rod-sliding and low pressure assisted solution processing composition engineering (GRS-LPASP), to manufacture high quality perovskite film in air. GRS-LPASP composition engineering effectively increases the grain size and thickness of perovskite films and reduces the defect density by increasing the contact area between the perovskite layer and the hole transport layer, thus leading an increased current density (Jsc) of perovskite solar cells. The device with GRS-LPASP composition engineering achieves a maximum PCE of 19.78%. The experimental results demonstrates that GRS-LPASP composition engineering is a feasible method to prepare high-efficiency PSCs. Moreover, GRS-LPASP composition engineering also provides a potential approach for the commercial production of PSCs.